A short total synthesis of (±)-mersicarpine via visible light-induced cascade photooxygenation. Issue 36 (13th April 2022) - Frahm, Mario; Voss, Alice; Brasholz, Malte
Abstract : A short synthesis of the Kopsia alkaloid (±)-mersicarpine is enabled by the visible light-driven photooxygenation of a tetrahydrocarbazole, generating a perhydropyrido[1, 2- a ]indole dione as the immediate precursor to the natural product. Abstract : A short total synthesis of the Kopsia alkaloid (±)-mersicarpine is presented. As the key step, a visible light-induced catalytic cascade photooxygenation was utilized, to convert a 3, 3-disubstituted tetrahydrocarbazole intermediate, in one step, into a perhydropyrido[1, 2- a ]indole dione as the immediate precursor to the natural product. The synthesis of mersicarpine was achieved with an overall yield of 12% over 13 steps.